IMPLEMENTATION MODEL OF CORPORATE SOCIAL RESPONSIBILITY IN INCREASING SOCIAL CAPITAL ON PT JEMARI KARYA MANDIRI - Halim Usman; Sumarno Sumarno; Andi Dahri AP (Magister Akuntansi, Universitas Atma Jaya Makassar, 2022)
Social capital is a set of informal values ​​or norms that are shared among members of a community group that are interrelated. A good measurement of social capital is when there is an agreement between the two parties, both the vision and goals of the organization have in common. Corporate Social Responsibility can be implemented through alternative models that can increase the social capital of the community, both from the economic, social, and cultural aspects in a sustainable manner. The purpose of this research is to determine the relationship between CSR implementation and increasing social capital of the community around the PT Jemari Karya Mandiri mine, as well as to find out the CSR implementation model of PT JKM in increasing the social capital of the community around the mine. The results of the study indicate that the implementation of the CSR model carried out by PT JKM is categorized as social capital because of one of the company's successes in business sustainability. Business sustainability can be seen from the organization's internal and external parties. The implementation of CSR which is categorized as social capital is when the company can convince the community that with the establishment of the company it can contribute to the community. A good measurement of social capital is when there is an agreement between the two parties, both the vision and goals of the organization have in common.